Anatomy and development of the reproductive units of Mapania pycnostachya and Hypolytrum schraderianum (Mapanioideae, Cyperaceae) - Monteiro, Mariana Maciel [UNESP] (2016)
The typical mapaniid reproductive unit, which comprises several bracts, stamens and a gynoecium, may be interpreted as a single flower. Although developmental studies suggest that the mapaniid reproductive units are inflorescences, the units in species such as Hypolytrum schraderianum Nees are much reduced and strongly resemble a single flower. Therefore, an anatomical and developmental study of the reproductive units of Mapania pycnostachya (Benth.) T. Koyama and H. schraderianum was conducted to better understand their structure. In both species, two lateral bracts (prophyll-like units) are the first to emerge, followed by staminal and gynoecial primordia. The reproductive units of M. pycnostachya have two inner bracts (leaf-like structures) that initiate after the stamens. In H. schraderianum, they are absent. In both species, the reproductive units have spiral phyllotaxy and staminal traces that join the vascular system of the reproductive-unit axis at different levels. The vasculature pattern of these units differs from the cyperoid flowers. Onthe basis of these results, it is inferred that the reproductive units of both species are inflorescences, composed of unisexual flowers. It is also inferred that this structure is the general pattern for Mapanioideae and that loss of male flowers and inner bracts has occurred during evolution of the subfamily.